Internalization of Religious Moderation Values in Multicultural Education - Maswan Ahmadi; Andi Aderus; Andi Jufri (Yayasan Rahmat Islamiyah, 2026)
This study examines the internalization of religious moderation values within the framework of multicultural education. In increasingly diverse societies, the rise of religious extremism and social intolerance poses significant challenges to communal harmony. Employing a qualitative research design based on content analysis and literature review, this paper analyzes the theoretical dimensions and practical strategies for embedding religious moderation into institutional policy, pedagogical methods, and school culture. The findings indicate that successful internalization relies on three primary pathways: formal curricular integration across disciplines, hidden curriculum practices exemplified by teacher modeling and inclusive campus climate, and experiential learning through intercultural and interfaith dialogue. Ultimately, synthesizing religious moderation with multicultural education transforms educational institutions into proactive incubators of peace, equipping learners to embrace diversity while upholding social cohesion and ethical balance.